Ensinar Ciência Geográfica : o processo lúdico de aprendizagem no 5º ano de uma escola pública de Parintins/AM. - Cordovil, Ronara Viana (2018)
The challenge of teaching lies in the possibilities of encouraging the student to read to learn and thus to project through the world of the adventure of knowledge in search of new foundations that base the learning. In order to enter this universe, the main objective was to understand the posture of social subjects, teachers and students of elementary school I, in the sense of construction and the evidence of teaching and learning through the playful, having as reference the school geography in communication with other disciplines, in a public school in the city of Parintins. The specific paths allowed to analyze the curricular proposals and the process of teaching and learning of the disciplines, and in particular, of geography, of elementary education I (5th Year); understand how the process of construction and preparation of teaching in the fundamental I occurs, taking the play as an alternative of learning in Geography and other disciplines in the public school of the city of Parintins and to present recommendations for a proposal of teaching and learning through the playful one that meets the the specificity of each discipline and consequently the understanding of local realities and other places in the relation of the local to the global, based on the findings obtained in the analysis of the results of the research techniques, for the purpose of later application. The theoretical basis of support can be found in: Andrade (2013); Calai (2012), Cavalcanti (2012); Zanata (2005) and Gadotti (2008) which present positions on the knowledge built in practice and in the daily practice. The methodological process to achieve the objectives was done through observations and in the practical exercise students in a circle and using their own body worked the movements of the Earth, orientations and location; the macaque (hopscotch) if worked the thermal zones of the Earth, latitude and longitude; the school's inaugural plaque as a source of history, geography, and science content; the relief was done in clipping and paper drawings. There is a growing demand for new techniques or teaching procedures to facilitate understanding of content, but it is necessary for the student to dedicate himself and commitment to the school. Faced with the reality of the school experience, the proposal of play as a process was used to give dynamism to the classroom and open spaces for analytical reflection as an alternative for the involvement of learners. It is important to emphasize that playfulness is not the only solution, but a teaching technique that must be exercised continuously. It is not play or play, but teach science content in the fifth year, through activities that enable the student to think, have a logical sequence of reasoning and make their notes from the understanding and understandings about a certain content taught in the classroom. Keywords: Geographic Science; Play Process; Teaching; Learning; Construction of Knowledge;